Loss and gain of carbon during char degradation. (March 2017) - Bird, Michael I.; McBeath, Anna V.; Ascough, Philippa L.; Levchenko, Vladimir A.; Wurster, Christopher M.; Munksgaard, Niels C.; Smernik, Ronald J.; Williams, Alan
Abstract: We report results of a study examining controls on the degradation of chars produced at 300, 400 and 500 °C from radiocarbon-free wood, deployed for three years in a humid tropical rainforest soil in north Queensland, Australia. The chars were subjected to four treatments (i) no litter (ii) covered by leaf litter, (iii) covered by limestone chips to alter local pH, and (iv) covered by limestone chips mixed with leaf litter. Radiocarbon, stable isotope and proximate analyses indicate significant ingress of exogenous (environmental) carbon and mineral material, strongly correlated with loss of indigenous (char) carbon from the samples. While indigenous carbon losses over three years were generally <8% for the char produced at 500 °C char under any treatment, chars formed at lower temperatures lost 5–22% of indigenous carbon accompanied by ingress of up to 7.5% modern exogenous carbon. The data provide clear evidence of a direct link between the ingress of exogenous carbon, likely at least partly due to microbial colonization, and the extent of char decomposition. Failure to account for the ingress of exogenous carbon will lead to a significant under-estimate of the rate of char degradation. Graphical abstract: Highlights: Radiocarbon-free char exposed to environmental degradation for 3 years. Loss and gain of carbon tracked by 13 C and 14 C. Chars lost up to 22% of indigenous carbon over 3 years. Chars gained up to 7.5% carbon from local environment. Trends determined by pyrolysis temperature and environmental conditions.